Immunogenicity of Bothrops atrox (Ophidia: Viperidae) venom and its evaluation by immunoenzymatic methods Inmunogenicidad del veneno de Bothrops atrox (Ophidia: Viperidae) y su evaluación por métodos inmunoenzimáticos - Gustavo A. Sandoval; Julio Mendoza; William Roldán; Yrma Espinoza; Hilda Solis; Armando Yarlequé (Revista Peruana de Biología, 2012)
The immunogenicity of Bothrops atrox, “jergón”, venom was studied using ELISA and Western Blot methods, as well as cross-reactivity patterns against venoms of Bothrops brazili, Lachesis muta and Crotalus durissus. For this purpose, New Zealand white rabbits (2 kg aprox) were immunized with four 500 μg doses of B. atrox venom in a period of 90 days. Antibody production was followed using ELISA technique, and title of hiper-immune serum was determined at the end of immunization protocol. Additionally, electrophoretic patterns of venoms were analyzed by SDS-PAGE and venom reactivity against obtained serum by ELISA and Western Blot. Immunization schedule allowed a pronounced antibody production since day 20 of protocol. At the end of process, serum title was 256000, which demonstrated both efficacy and usefulness of the developed procedure. On the other hand, studied venoms showed a heterogenic protein composition according to their electrophoretic patterns, whereas cross-reactivity values of 23,7%, 4,0% and 1,8% were obtained between B. atrox venom and B. brazili, L. muta and C. durissus venoms, respectively, using immunoenzymatic methods. According to our results, this procedure constitutes an initial step for further assays directed to optimization in immunoserum production for envenoming treatment and development of kits for diagnosis and species identification of snakes. Se estudió la inmunogenicidad del veneno de la serpiente Bothrops atrox, “jergón”, utilizando los métodos inmunoenzimáticos de ELISA y Western Blot, así como los patrones de reactividad cruzada empleando los venenos de las serpientes Bothrops brazili, Lachesis muta y Crotalus durissus. Para este fin se inmunizaron conejos albinos Nueva Zelanda (2 kg aprox) con cuatro dosis de 500 μg del veneno de B. atrox en un periodo de 90 días. La producción de anticuerpos fue monitoreada mediante la técnica de ELISA, determinándose el título del suero hiperinmune obtenido al final del protocolo de inmunización. Adicionalmente se analizaron los patrones electroforéticos de los venenos en estudio mediante PAGE-SDS y su reactividad frente al suero obtenido mediante ELISA y Western Blot. El esquema de inmunización utilizado permitió una producción sostenida de anticuerpos a partir del día 20 del protocolo. Finalizado este proceso, el título del suero fue calculado en 256000, lo cual mostró la eficacia y practicidad del procedimiento desarrollado. Por otro lado, los venenos estudiados mostraron una heterogeneidad en su composición proteica a partir del análisis de sus patrones electroforéticos, mientras que a partir de los estudios inmunoenzimáticos, se pudo obtener valores de reactividad cruzada entre el veneno de B. atrox y los venenos de B. brazili, L. muta y C. durissus, de 23,7%, 4,0% y 1,8%, respectivamente. Los resultados obtenidos constituyen el paso inicial para posteriores ensayos dirigidos a la optimización en la producción de inmunosueros para el tratamiento del envenenamiento, así como para el desarrollo de kits de diagnóstico e identificación de especies de serpiente.